Study finds correlation between high unemployment rates and gun violence on campus. Issue 12 (April 2017) - Sutton, Halley
Abstract : A correlation between gun violence and unemployment rates was found in a study conducted by Northwestern University and published in the journal Nature Human Behaviour . The study found that the probability of gun violence at K–12 schools and higher education institutions increases when it is more difficult for people coming out of schools to secure jobs. The study, entitled "Economic Insecurity and the Rise in Gun Violence at US Schools, " analyzed data on statistics on gun violence in schools, as well as economic metrics including unemployment rates, foreclosure rates, and consumer confidence from the years 1990 to 2013.